Characteristics of interpersonal violence in adult victims at the Adult Emergency Trauma Centre (AETC) of Queen Elizabeth Central Hospital - Sheikh, Shabnam (Malawi Med J, 2020)
INTRODUCTION: Globally, the burden of interpersonal violence and its significant impact on mortality, morbidity and disability makes it a major public health problem which necessitates intervention. This article examines characteristics of victims of interpersonal violence and violent events in Malawi. The focus is on a population that has been traditionally neglected in literature. METHODS: Queen Elizabeth Central Hospital (QECH) maintains a trauma registry with data that is prospectively collected. Patients offered trauma care after interpersonal violence from May 2013 to May 2015 were evaluated. RESULTS: There were 1431 patients with violent events recorded at the Adult Emergency Trauma Centre (AETC) with a male predominance of 79.5%. The dominant age group was young adults between 25–29 years old (22%). Most attacks occurred during cold and dry season (46.9%) and most common location was on the road (37.2%). Alcohol use by victims was recorded in 10.5% of cases. Soft tissue injuries were the most common injuries sustained (74.1%). Most patients were treated as outpatients (80.9%). There were two deaths. At multivariate analysis, women had a lower risk of interpersonal violence as compared to men, (OR 0.82 [0.69–0.98]). Victims' use of alcohol was associated with increased risk of assault (OR 1.63 [1.27–2.10]). As compared to other places, odds of being assaulted were higher at home (OR 1.62 [1.27–2.06]) but lower at work (OR 0.68 [0.52–0.89) and on the road (OR 0.82 [0.65–1.03]). Odds of being assaulted were higher in the cold and dry season as compared to hot and dry season, (OR 1.26 [1.08–1.47]). CONCLUSION: Young males were most involved in interpersonal violence. Location of injury and seasonal variation were significant factors associated with interpersonal violence and most commonly sustained injuries were soft tissue injuries. These findings will help in identifying targeted interventions for interpersonal violence in Malawi and other low-and-middle-income countries (LMICs).